Pendampingan Kader Puskesmas Dalam Pengelolaan Limbah Rumah Tangga Sebagai Kompos - Maksuk; Lukman (Universitas Lancang Kuning, 2020)
The cadres of public health center have an important role in managing of households in the community, therefore it is important to improve skills to manage such waste so that the waste can be utilized and beneficial. The method of managing household waste in this activity uses the concept of Pilah – Kumpul - Manfaat - Untung (PKMU) to reduce the volume of household waste and provide benefits to the community. Participants involved in this activity were health workers, kader of community health centers and the community of RT 14 and RT 33. The Achievement targets in this activity were to improve the ability of health workers and cadres to manage of household waste, use of household waste for the planting of medicinal plants, families and the formation of independent care working groups for batra activities in health center and the formation of waste bank managers. The results of this activity show that cadres and the community can use household waste as compost, in addition, household waste such as plastic can be reused. The follow up of this activity is the formation of a waste bank manager at the location of the activity.